2014
DOI: 10.1002/2013ja019299
|View full text |Cite
|
Sign up to set email alerts
|

Effect of plasma torus density variations on the morphology and brightness of the Io footprint

Abstract: We develop a 2-D-layered model of the Io plasma torus to study the apparent "shutoff" of the Io footprint in 2007, when it disappeared beneath a region of diffuse emissions, roughly coincident with a massive eruption of Tvashtar Paterae. First, we investigate the effects of Io's location in the plasma torus and validate our model results against Hubble UV observations of the Io footprint. We are able to qualitatively reproduce variations in the morphology of the footprint due to Io's changing latitudinal locat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…On this set of FUV images, the IFP nearly disappears as it crosses the blob before re-emerging outside of it. The model of Payan et al (2014) explains this behavior through a localized increase of the torus density resulting in a stronger trapping of the Alfvén waves within the torus. Another study by Hess et al (2013b ) also agrees that an increased torus density would decrease the wave transmission across the torus boundary.…”
Section: Introductionmentioning
confidence: 99%
“…On this set of FUV images, the IFP nearly disappears as it crosses the blob before re-emerging outside of it. The model of Payan et al (2014) explains this behavior through a localized increase of the torus density resulting in a stronger trapping of the Alfvén waves within the torus. Another study by Hess et al (2013b ) also agrees that an increased torus density would decrease the wave transmission across the torus boundary.…”
Section: Introductionmentioning
confidence: 99%
“…The dispersal of plasma from the IPT into the rest of the magnetosphere is the main process that provides plasma to the rest of Jupiter's magnetosphere. Therefore spatial and temporal variations in the IPT can ultimately affect the distribution and dynamics of plasma throughout Jupiter's entire magnetosphere [Bonfond et al, 2012;Payan et al, 2014].…”
mentioning
confidence: 99%
“…Jovian decametric emission is variable but predictable. The strongest bursts come from the Io-driven sources, which depend on the longitude of Jupiter and orbital phase of Io (Bigg 1964;Payan 2014). In Romero-Wolf et al 2015, it was shown that the Iodriven source is compact enough (Dulk 1970;Carr et al 1970;Lynch et al 1976) to be treated effectively as a point source for the purposes of sounding.…”
mentioning
confidence: 99%